AN IMPROBABLE APHRODISIACINTHE CRISIS OF SEXUALITY:WHAT ARE THE IMPLICATIONS? - Fred A. Amadi (European Scientific Journal, ESJ, 2015)
Given the rising wave of violentacts across the world, this paper is designed to investigate the improbable but emerging trend which seems to suggest that violent behavior now appears to be an incentive when dating and even marriage decisions are made. The investigation is carried out with a pool of data made up of multiple variants. After displaying the data in a textbox, subjective valuing was usedto attribute certain phenomena to segments of the data. After affirming that females consider violent traits in males as incentives in their male-partner preferences, data representation failed to establish a decisive link between fierce delinquent acts and sexual frustration.